Facial race and sex cues have a comparable influence on emotion recognition in Chinese and Australian participants - Craig, Belinda; Zhang, J.; Lipp, Ottmar (Springer, 2017)
The magnitude of the happy categorisation advantage, the faster recognition of happiness than negative expressions, is influenced by facial race and sex cues. Previous studies have investigated these relationships using racial outgroups stereotypically associated with physical threat in predominantly Caucasian samples. To determine whether these influences generalise to stimuli representing other ethnic groups and to participants of different ethnicities, Caucasian Australian (Experiments 1 and 2) and Chinese participants (Experiment 2) categorised happy and angry expressions displayed on own-race male faces presented with emotional other-race male, own-race female, and other-race female faces in separate tasks. The influence of social category cues on the happy categorisation advantage was similar in the Australian and Chinese samples. In both samples, the happy categorisation advantage was present for own-race male faces when they were encountered with other-race male faces but reduced when own-race male faces were categorised along with female faces. The happy categorisation advantage was present for own-race and other-race female faces when they were encountered with own-race male faces in both samples. Results suggest similarity in the influence of social category cues on emotion categorisation.